EMPIRICAL STUDY OF FEATURES OF SOCIAL- PSYCHOLOGICAL ADAPTATION OF YOUTH DURING MILITARY ACTIONS IN UKRAINE (Psychology Travelogs, 2023)
This article reveals the features of the concept of social and psychological adaptation. It was determined that socio-psychological adaptation is a process of mutual exchange of information about socio-psychological characteristics between the work team and the individual, establishing contacts and relationships on this basis, which provide the possibility of effective joint work and informal communication. Social events taking place in the world and in the country force young men and women to make their own choices, to orientate themselves in everything. The main neoplasm of youth is personal self-determination, on which all other types of self-determination of young men and women depend. The main socio-psychological determinants of the personal self-determination of young men and women, which are meaningful, include: the importance of problems discussed with peers; circle of reference persons; value orientations; purposefulness of relationships; areas of self-realization; attitude to society and self-understanding in it; future plans, their specific content; choosing a profession, focusing on socially or personally significant factors in it; a measure of confidence in choosing a course of action. The theoretical foundations of the study of maladaptation trends at this age stage are numerous qualitative shifts in the physiological, mental, and social aspects of a young person's development in this period. In this work, young people who are in a state of socio-economic crisis - the war in Ukraine - were studied.
Keywords: youth; socio-psychological adaptation; socio-political crisis; destructive long-term strategic life attitudes and value orientations